Gorham-Stout Disease Resulting in Spinal Deformity Treated by Fusion Surgery Combined With Everolimus Therapy: A Case Report. Issue 1 (January 2021) - Toga, Akira; Watanabe, Kota; Suzuki, Satoshi; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Okada, Eijiro; Yagi, Mitsuru; Fujita, Nobuyuki; Nakamura, Masaya; Matsumoto, Morio
Abstract : Case: Gorham-Stout disease (GSD) is a rare disorder characterized by progressive localized osteolysis and lymphatic malformation. A 26-year-old woman with GSD presented to our hospital with a Cobb angle of 100° and a kyphosis angle of 88°. Everolimus therapy was initiated to control the disease prior to surgery. After halo-gravity traction for 4 weeks, we performed anterior and posterior spinal fusion. Postoperative computed tomography revealed satisfactory bone union and no significant loss of correction 1 year post-surgery. Conclusion: This case suggests that anterior and posterior spinal fusion combined with everolimus therapy can be a therapeutic option for GSD.